Standardized freeze-dried FMT: is the ideal protectant out there? - Pourrat, Alix; Baillieu, Vinciane; Ansel, Solene; Leonardi, Maxime; Poiron, Pierre; Bellais, Samuel; Paul, Muriel; Nebbad, Biba (Frontiers in Microbiology, 2025)
BackgroundFecal microbiota transplantation (FMT) is an effective treatment for recurrent Clostridioides difficile infections. Freeze-drying offers a next-generation, more practical, and aesthetically acceptable FMT formulation that could facilitate standardized preparation methods. Viable preservation is a critical step in freeze-drying, yet no universal medium effectively protects both anaerobes and aerobes.ObjectiveThis study aimed to evaluate different protectants compared to trehalose 5% (T5) after confirming its efficacy.MethodsA mix of inulin and glucosamine (IG5) and a High-antioxidant Matrix with trehalose (HM) were tested. Viability was assessed using colony-forming unit (CFU) enumeration and flow cytometry with a LIVE/DEAD™ staining method.ResultsT5 demonstrated satisfactory bacterial recovery after freeze-drying, with viability of 84 ± 28% for anaerobes and 59 ± 39% for Bifidobacterium (BIF), confirming its efficiency in our preparation facilities. While HM showed highest results (91 ± 7% for anaerobes, 121 ± 33% for BIF), it did not significantly outperform T5. IG5, however, resulted in a significant loss of bacteria, with only 16 ± 12% viability for anaerobes (p = 0.016) and 19 ± 9% for BIF (p = 0.031).ConclusionHM and T5 both proved effective for freeze-dried FMT, with HM yielding the highest recovery but not significantly outperforming T5. Given its simplicity and consistent results, T5 may serve as a reliable standalone protectant or as a base for improved formulations. IG5 showed significant bacterial loss and is unsuitable. Further biological validation and stability data will guide the development of optimized freeze-dried oral FMT capsules.